2006
DOI: 10.1073/pnas.0602002103
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1 transcripts are differentially expressed in schizophrenia and regulated by 5′ SNPs associated with the disease

Abstract: Genetic variation in neuregulin 1 (NRG1) is associated with schizophrenia. The disease-associated SNPs are noncoding, and their functional implications remain unknown. We hypothesized that differential expression of the NRG1 gene explains its association to the disease. We examined four of the disease-associated SNPs that make up the original risk haplotype in the 5 upstream region of the gene for their effects on mRNA abundance of NRG1 types I-IV in human postmortem hippocampus. Diagnostic comparisons reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
214
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 374 publications
(231 citation statements)
references
References 46 publications
6
214
0
Order By: Relevance
“…In particular, altered NRG1 expression, rather than loss of function, has been associated with this disease (54). Consistent with this finding, a number of groups have observed altered expression patterns for various NRG1 isoforms (54 -56).…”
Section: Discussionsupporting
confidence: 65%
“…In particular, altered NRG1 expression, rather than loss of function, has been associated with this disease (54). Consistent with this finding, a number of groups have observed altered expression patterns for various NRG1 isoforms (54 -56).…”
Section: Discussionsupporting
confidence: 65%
“…Hashimoto et al (12) examined type I-III NRG1 transcripts in the dorsolateral prefrontal cortex and found increased NRG1 type I mRNA in schizophrenia, a finding that was subsequently confirmed in a separate and larger sample in the hippocampus (10). However, evidence for a relationship between genetic risk in the gene and increased expression of type I mRNA in the brain was inconclusive.…”
Section: Neuregulin 1 (Nrg1)mentioning
confidence: 97%
“…The association with schizophrenia was first reported in an Icelandic population in which a NRG1 haplotype (Hap ice ) consisting of five single nucleotide polymorphisms (SNPs) and two microsatellites covering the 5Ј-end of the gene doubled the risk for the disorder (9). Four of these SNPs (SNP8NRG221132, SNP8NRG221533, SNP8NRG241930, and SNP8NRG243177 (rs6994992)) represent a 22-kb surrogate haplotype that resides in the 5Ј flanking putative promoter region of NRG1 directly upstream of the novel E187 exon, which is unique to the NRG1 type IV isoform (7,10). Follow-up studies in multiple ethnic populations and a meta-analysis have confirmed genetic association between schizophrenia and NRG1 using markers within the same core haplotype (8,11) or with overlapping markers in the 5Ј region, making NRG1 a leading schizophrenia susceptibility gene.…”
Section: Neuregulin 1 (Nrg1)mentioning
confidence: 99%
“…Our results indicate that loss of NRG1-erbB signaling in OLs may contribute to these diseases. Thus, the possibility that the reported increases in NRG1 or erbB4 expression (4,5,34,35) or erbB4 activation (36) reflect a compensatory response to a loss/reduction in function in this signaling pathway needs to be considered. This signaling pathway may also contribute to neuropsychiatric disorders through nongenetic mechanisms because both NRG1 and erbB4 expression have been shown to be altered by environmental insults (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%